Differential time‐dependent volumetric and surface area changes and delayed induction of new permeation pathways in P. falciparum‐infected hemoglobinopathic erythrocytes. (25th August 2016) - Waldecker, Mailin; Dasanna, Anil K.; Lansche, Christine; Linke, Marco; Srismith, Sirikamol; Cyrklaff, Marek; Sanchez, Cecilia P.; Schwarz, Ulrich S.; Lanzer, Michael
Abstract: During intraerythrocytic development, Plasmodium falciparum increases the ion permeability of the erythrocyte plasma membrane to an extent that jeopardizes the osmotic stability of the host cell. A previously formulated numeric model has suggested that the parasite prevents premature rupture of the host cell by consuming hemoglobin (Hb) in excess of its own anabolic needs. Here, we have tested the colloid‐osmotic model on the grounds of time‐resolved experimental measurements on cell surface area and volume. We have further verified whether the colloid‐osmotic model can predict time‐dependent volumetric changes when parasites are grown in erythrocytes containing the hemoglobin variants S or C. A good agreement between model‐predicted and empirical data on both infected erythrocyte and intracellular parasite volume was found for parasitized HbAA and HbAC erythrocytes. However, a delayed induction of the new permeation pathways needed to be taken into consideration for the latter case. For parasitized HbAS erythrocyte, volumes diverged from model predictions, and infected erythrocytes showed excessive vesiculation during the replication cycle. We conclude that the colloid‐osmotic model provides a plausible and experimentally supported explanation of the volume expansion and osmotic stability of P. falciparum ‐infected erythrocytes. The contribution of vesiculation to the malaria‐protective function of hemoglobin S is discussed.